Quantum geometry and nanophotonic enriched nonlinear photoresponse in van der Waals materials - Xiong, Ying (Nanyang Technological University, 2022)
The quantum geometry of Bloch wavefunctions is a fundamental property of quantum materials that can have a profound impact on its response. I will discuss how quantum geometry can strongly modulate nonlinear optical responses such as photocurrents, enabling a novel macroscopic probe for atomic configuration in van der Waals homostructures. I will also discuss how nonlinear photoresponse can be greatly enriched by nanophotonic technologies via interaction with highly confined photonic/polaritonic modes. Such nonlinear light-matter interactions can enable the probing of momentum-resolved quantum geometry using photocurrents as well as sustain new dynamical phases of matter that have no simple analogue in equilibrium.